Attributes of excellent clinician teachers and barriers to recognizing and rewarding clinician teachers’ performances and achievements: A narrative review - Wondwossen Fantaye, Arone; Kitto, Simon; Hendry, Paul; Wiesenfeld, Lorne; Whiting, Sharon; Gnyra, Catherine; Fournier, Karine; Lochnan, Heather (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Background: Over the last 31 years, there have been several institutional efforts to better recognize and reward clinician teachers. However, the perception of inadequate recognition and rewards by clinician teachers for their clinical teaching performance and achievements remains. The objective of this narrative review is two-fold: deepen understanding of the attributes of excellent clinician teachers considered for recognition and reward decisions and identify the barriers clinician teachers face in receiving recognition and rewards.Methods: We searched OVID Medline, Embase, Education Source and Web of Science to identify relevant papers published between 1990 and 2020. After screening for eligibility, we conducted a content analysis of the findings from 43 relevant papers to identify key trends and issues in the literature.Results: We found the majority of relevant papers from the US context, a paucity of relevant papers from the Canadian context, and a declining international focus on the attributes of excellent clinician teachers and barriers to the recognition and rewarding of clinician teachers since 2010. ‘Provides feedback’, ‘excellent communication skills’, ‘good supervision’, and ‘organizational skills’ were common cognitive attributes considered for recognition and rewards. ‘Stimulates’, ‘passionate and enthusiastic’, and ‘creates supportive environment’, were common non-cognitive attributes considered for recognition and rewards. The devaluation of teaching, unclear criteria, and unreliable metrics were the main barriers to the recognition and rewarding of clinician teachers.Conclusions: The findings of our narrative review highlight a need for local empirical research on recognition and reward issues to better inform local, context-specific reforms to policies and practices.